A three-dimensional MRI study of variations in central sulcus location in 40 normal subjects - Hamasaki, Tadashi; Imamura, Jun-ichi; Kawai, Hiroshi; Kuratsu, Jun-ichi (Journal of clinical neuroscience, 2012)
We used a computational strategy, in vivo morphometry, to evaluate structural magnetic resonance (MR) images to investigate individual variations in the location of the central sulcus (CS). To locate the CS we identified six key points on individual brain images obtained from 40 normal subjects and measured the distances between these points along the brain circumference. We also analyzed the difference between the actual location of the CS and the location predicted by conventional estimation methods. Individual variation exceeded 2.7 cm for all measurements used to identify the location of the CS. The margin of error was approximately 2.7 cm even when the location of the CS was predicted by reported and commonly used methods. A “1 inch error” should be taken into consideration when the prediction relies solely on head circumference and surface measurements. Our results point to the importance of pre-surgical planning using individual brain images for each patient.